Highly enhanced sinterability of fine-grained Ba0.6Sr0.4TiO3−MgO bulk ceramics and in-situ nanocomposite thick films - Chan, Helen Lai-Wa (2014)
Well-developed, dense and fine-grained MgO–(Ba0.6Sr0.4)TiO3 with 40 wt% MgO content (denoted as BST–MgO) bulk ceramics were fabricated by high-energy ball mechanochemical technique using a hybrid processing. Based on this technique, the fabrication temperature was as low as 1200 °C i.e., 200 °C lower than that required by using conventional solid-state process. At the same time, dense, homogeneous and crack-free ceramic–ceramic 0–3 nanocomposite BST–MgO thick film was obtained at 700 °C using the spin-coating method. At 10 kHz and room temperature, the BST–MgO bulk ceramics exhibited a moderate dielectric constant of about 500 and low loss tangent of less than 0.005; while for the nanocomposite thick films, the dielectric constant and loss tangent were about 140 and less than 0.03 (at 100 kHz) respectively. In addition, both the bulk ceramics and thick film show a broad and diffused phase transition. The dielectric room-temperature tunabilities measured at 100 kHz were found to be 4% at 1.5 kV/mm for the bulk ceramic, and 17% at 10 kV/mm for nanocomposite thick film.